Awareness of the association between obesity and peri-operative risk among newly diagnosed patients with complex atypical hyperplasia and endometrial cancer - Lindsay M. Kuroki; Teri E. Benn; Jonathan L. Dukes; Andrea R. Hagemann; Premal H. Thaker; Matthew A. Powell; David G. Mutch; L. Stewart Massad; Israel Zighelboim (Elsevier, 2015)
Objectives: The aim of this study is to evaluate knowledge of obesity-related peri-operative risks in women newly diagnosed with complex atypical hyperplasia and endometrial cancer. Methods: We conducted a cross sectional study of patients newly diagnosed with complex a typical hyperplasia or endometrial cancer who underwent preoperative counseling between 2011 and 2014, using a 17-item questionnaire. Obesity was defined as body mass index (BMI) of 30 kg/m2 or greater. Bivariate analysis was conducted using Pearson's Chi-Square or Fisher's Exact tests where appropriate and Mann-Whitney U for continuous variables. Results: Of 98 patients recruited, mean age was 58 years, 87% were obese, 83% white, and 51% had grade 1 endometrioid adenocarcinomas. Sixty-four percent of obese women reported that their physicians had discussed surgical risks related to obesity. However, 17% of obese and 42% of non-obese patients responded that they were unsure of the peri-operative risks associated with obesity. There was a substantial lack of understanding among obese patients regarding their increased risks of respiratory problems (29%), thromboembolism (29%), heart attack (35%), or longer operating time (35%) and hospital stay (47%). However, obese patients were more aware of wound infection risks associated with obesity compared to their non-obese counterparts (72% vs. 31%, p = 0.004). Conclusions: Pre-operative counseling for obese women with newly diagnosed endometrial cancer should incorporate more focused education about obesity-related risks. They report being knowledgeable about the risks associated with their surgery; however, more than a quarter are unaware of the impact obesity has on respiratory problems, thromboembolism, wound infection, heart attack or longer operating time and hospital stay.